Virtual Reality dan Leap Motion Controller sebagai Terapi Fisik pada Pasien Pasca Stroke: Sebuah Literature Review - Tsani, Elfrida Riani (Prosiding University Research Colloquium, 2022)
Stroke is a malfunction of the nerves caused by circulatory disorders of the brain. Recovery of post-stroke patients will be hampered by lack of physical exercise so that it can cause dependence, disability and even death. The application of physical exercise is used to overcome paralysis in stroke patients.-based Virtual Reality technology is a technology that is created in the form of a 3-dimensional tool that is controlled by software so that it looks like real. Leap Motion Controller (LMC) game is a technology that can be used as a muscle recovery therapy in the upper extremities. This research is a study to look specifically at the effect of Virtual Reality and Leap Motion Controller as therapy for post-stroke patients..Methods: This research was written as a literature review with a narrative analysis method using databases including PubMed, ScienceDirect, Google Scholar. Results: At the article collection stage, 3,347 titles were obtained from 3 search engines. After doing the screening, the authors found 29 articles that matched and met the requirements. From the data obtained, it can be concluded that the Leap Motion Controller and Virtual Reality can be used as virtual reality games for physical therapy in post-stroke patients.